Pengaruh Dompet Digital dan Kualitas Produk terhadap Niat Beli Konsumen (Studi : Geprek MB Bandar Lampung) - Hidayat, Rifki; Alfarezi, Muhammad; Umar, M Abdullah (STIES ALIFA, 2024)
This study aims to determine the effect of digital wallets and product quality on consumer purchase intentions in Geprek MB Lampung. Consumer purchase intention is an attitude of a consumer or potential customer who tends to be interested then makes a decision to spend on the goods or services he wants. This research is of the quantitative type. The population in this study is all customers of all Geprek MB Bandar Lampung consumers during the observation period, which is one month. The total population was 10,985 consumers while for the sample with the solvin technique, 111 respondents were obtained. The result of this study is that partially, digital dmpet and product quality have a positive effect on consumer purchase intent, while simultaneously digital wallets and product quality also have a positive and significant influence on consumer purchase intent.